PENGARUH EXPERIENTIAL MARKETING DAN BRAND TRUST TERHADAP LOYALITAS KONSUMEN LAZADA PADA MAHASISWA INSTITUT STIAMI FAKULTAS ILMU ADMINISTRASI ANGKATAN TAHUN 2018 - Antoni Ludfi Arifin (Jurakunman (Jurnal Akuntansi dan Manajemen), 2022)
This study conducted an analysis of the Effect of Experiential Marketing and Brand Trust towards Lazada Consumer Loyalty on Institut STIAMI Students - Faculty of Administrative Sciences 2018. This study aimed to empirically examine the effect of Experiential Marketing and Brand Trust on Consumer Loyalty. The independent variables in this study are Experiential Marketing and Brand Trust, and the dependent variable is Consumer Loyalty.This study was using quantitative method with a population of 768 students from the Student of Institut STIAMI - Faculty of Administrative Sciences 2018 and a sample of 115 respondents using the Suharsimi Arikunto formula, with the accidental sampling technique as the non-probability sampling method. The data was processed by SPSS data statistical analysis ver.24.The results of the study indicates that there is a simultaneous positive and significant effect between Experiential Marketing and Brand Trust variables on Consumer Loyalty, which the f-count value is 19,137, and the coefficient of determination for Experiential Marketing and Brand Trust on Consumer Loyalty on Insitut STIAMI Students - Faculty of Administrative Sciences 2018, which is 25.5%, while the remaining 74.5% is determined by other variables that are not calculated in this study.